227k views
0 votes
Select the correct product.

(x 2 + 4x + 8)(2x - 1)

User Ohe
by
4.3k points

2 Answers

3 votes

Answer:


\large\boxed{(x^2+4x+8)(2x-1)=2x^3+7x^2+12x-8}

Explanation:

Use FOIL: (a + b)(c + d) = ac + ad + bc + bd


(x^2+4x+8)(2x-1)\\\\=(x^2)(2x)+(x^2)(-1)+(4x)(2x)+(4x)(-1)+(8)(2x)+(8)(-1)\\\\=2x^3-x^2+8x^2-4x+16x-8\qquad\text{combine like terms}\\\\=2x^3+(-x^2+8x^2)+(-4x+16x)-8\\\\=2x^3+7x^2+12x-8

User Martin Revert
by
4.9k points
2 votes

Answer:

The correct answer

(x² + 4x + 8)(2x - 1) = 2x³ + 7x² + 12x - 8

Explanation:

It is given that, (x² + 4x + 8)(2x - 1)

Points to remember

xᵃ * xᵇ = xᵃ⁺ᵇ

To find the product

(x² + 4x + 8)(2x - 1) = [(x²*2x) + (4x *2x) (8*2x)] - [x² + 4x + 8]

= 2x³ + 8x² + 16x - x² - 4x -8

= 2x³ + 8x² - x² + 16x - 4x -8

= 2x³ + 7x² + 12x - 8

User Matovu Ronald
by
5.3k points